2008
DOI: 10.1021/jp803437v
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Properties of Well-Dispersed Nanopolyaniline/Epoxy Hybrids Prepared Using an Absorption-Transferring Process

Abstract: Novel polyaniline (PANI)/epoxy hybrids have been fabricated using an absorption-transferring process in which no organic solvent is involved. An epoxy prepolymer cured by aniline monomer (DGEBA-aniline) was added to a freshly prepared PANI nanoparticles (NPs) aqueous solution with vigorous agitation and heating (ca. 90 °C). The PANI NPs were absorbed on the surface of epoxy droplet and then transferred into the whole droplet. The microstructures of the product PANI/epoxy hybrids, characterized using scanning e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 28 publications
1
38
0
Order By: Relevance
“…Polyaniline has emerged as one of the most promising conducting organic polymers, owing to its high polymerization yield, good environmental stability, moderate electrical conductivity and relatively low production cost. Recently, we have worked on developing high dielectric permittivity nano-composites systems, such as PANI-DBSA/PU(polyurethane), 29 PANI-DBSA/ PAA, 30 and PANI-DBSA/epoxy, 31 for the applications in the fields of energy storage, integral capacitor technology, electro-active devices and electromagnetic interference(EMI). In these studies, negative ε values have been observed when we follow certain synthetic routes and fabrication procedures.…”
Section: Copyright 2012 Author(s) This Article Is Distributed Under mentioning
confidence: 99%
See 1 more Smart Citation
“…Polyaniline has emerged as one of the most promising conducting organic polymers, owing to its high polymerization yield, good environmental stability, moderate electrical conductivity and relatively low production cost. Recently, we have worked on developing high dielectric permittivity nano-composites systems, such as PANI-DBSA/PU(polyurethane), 29 PANI-DBSA/ PAA, 30 and PANI-DBSA/epoxy, 31 for the applications in the fields of energy storage, integral capacitor technology, electro-active devices and electromagnetic interference(EMI). In these studies, negative ε values have been observed when we follow certain synthetic routes and fabrication procedures.…”
Section: Copyright 2012 Author(s) This Article Is Distributed Under mentioning
confidence: 99%
“…30,31 Figure 2 depicts the variation of ε of PANA-DBSA/PAA nano-composites, plotted with respected to PANI contents and the AC frequencies applied. The results show that a negative ε was obtained for all the nano-composites containing more than 6 wt% of PANI.…”
Section: Copyright 2012 Author(s) This Article Is Distributed Under mentioning
confidence: 99%
“…[11,12,16,17] Moreover, their negative permittivity and/or negative permeability were considered to be caused solely by those inorganic inclusions, and were independent of the polymer properties. In a recent study, on nanopolyanilne/ epoxy hybrids obtained by a special absorption-transferring process, [18] the occurrence of negative permittivity was considered to have resulted from the formation of a continuous conductive network of conductive polymer, polyaniline.Our latest studies of polymer nanocomposites prepared in our facilities surprisingly showed negative permittivity values. It has been discovered that the negative permittivity can be obtained from lab-fabricated non-metallic nanocomposites by a conventional solution-processing method, without any specially designed structures within the nanocomposites.…”
mentioning
confidence: 99%
“…This indicates that the conductivity of PEI/CNF nanocomposites can be considered to be unrelated to the negative permittivity, which is inconsistent with the results of the nanopolyaniline/epoxy hybrids. [18] According to the microstructures of the film samples of both PEI nanocomposites (Fig. 2), the changes of structures and Figure 1.…”
mentioning
confidence: 99%
“…All the SU-8/PPy-GOs nanocomposites show higher ε΄ and ε΄΄ than pure SU-8 and the values of both permittivities increase with increasing the loading of the PPy-GO nanofillers. The enhanced permittivity was widely observed in the nanocomposites and was attributed to the interfacial polarization in which the charge carriers were blocked at the internal surface or at interfaces between the matrix and the fillers leading to an increased permittivity [24,25]. In the SU-8/PPy-GOs, although the protons (hydrogen ions) provided by the doping acid can move along the PPy chains, these charge movements will be hindered by SU-8 resin, thus, a large number of space charges will accumulate at the interface of PPy and SU-8 and result in a larger interfacial polarization.…”
Section: Electrical Propertiesmentioning
confidence: 99%